Chronic and recurrent meningitis. Issue 6 (17th November 2008) - Ginsberg, L; Kidd, D
Abstract : Chronic meningitis is defined as the persistence of clinical symptoms and signs of meningitis, with or without abnormal cerebrospinal fluid, for more than four weeks. In as many as one third of cases, no cause is found. In the remainder, infective, neoplastic and so-called aseptic disorders may be identified. Important infective causes include partially treated bacterial (pyogenic), tuberculous, syphilitic, Lyme and fungal meningitis. Sarcoidosis, Behçet's disease, vasculitis and drugs are major non-infective, non-malignant causes. The definitive diagnosis of the cause of chronic meningitis may be made only after extensive investigation. This review describes the clinical features and causes of chronic and recurrent meningitis, and provides an algorithm for investigation and treatment.